Caracterización geohidrológica con tomografía eléctrica del parqueadero de la universidad Antonio Nariño sede Usme (2022)
In the locality of Usme seeks to generate and strengthen organizational and construction processes, a project called “New Usme Strategic Operation – Axis of Integration Llanos” was established, where several partial plans were established, in the case of polygon 3 of the Zonal Development Plan, which corresponds to the location of the Antonio Nariño University, the partial plan “ecological technology park” was generated, to support the growth of the locality. In order to contribute geophysical studies to the existing documents on the soil of the University, the realization of this research project aims to characterize the soil of a part of the University Antonio Nariño, specifically the area of the parking lot, using two resistivity methods, Wenner and Schlumberger Vertical Electric Sounding, by means of electric tomography: